2012
DOI: 10.1016/j.neurobiolaging.2011.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of cPLA2 in Aβ oligomer-induced neurodegeneration and memory deficit

Abstract: Soluble beta-amyloid (A␤) oligomers are considered to putatively play a critical role in the early synapse loss and cognitive impairment observed in Alzheimer's disease. We previously demonstrated that A␤ oligomers activate cytosolic phospholipase A 2 (cPLA 2 ), which specifically releases arachidonic acid from membrane phospholipids. We here observed that cPLA 2 gene inactivation prevented the alterations of cognitive abilities and the reduction of hippocampal synaptic markers levels noticed upon a single int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
58
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(66 citation statements)
references
References 72 publications
8
58
0
Order By: Relevance
“…Disturbance of membrane structures can also impede the transport and clearance of neurotoxic amyloid peptides ( 42,43 ). PLA 2 products have infl ammatory properties that can exacerbate the damage to brain tissues ( 44,45 ). Thus, the increase in PLA 2 activity that we measured in CSF may be expected to worsen LOAD pathophysiology by destroying cell membranes or by generating infl ammatory molecules.…”
Section: Role Of Gp Metabolism In Clinical Groupsmentioning
confidence: 94%
“…Disturbance of membrane structures can also impede the transport and clearance of neurotoxic amyloid peptides ( 42,43 ). PLA 2 products have infl ammatory properties that can exacerbate the damage to brain tissues ( 44,45 ). Thus, the increase in PLA 2 activity that we measured in CSF may be expected to worsen LOAD pathophysiology by destroying cell membranes or by generating infl ammatory molecules.…”
Section: Role Of Gp Metabolism In Clinical Groupsmentioning
confidence: 94%
“…This animal model has been used widely to test drug candidates for AD and has been consistently shown to induce cognitive impairment and neurodegeneration [21][22][23][24]. There were no cognition deficits using NORT (duration of sniffing novel object) apparent 1 week after the injection of Aβ (Fig.…”
Section: Three-month-old Tau Ko Mice Are Resistant To Aβ Toxicitymentioning
confidence: 97%
“…The A ␤ peptides that are implicated in Alzheimer's neurodegeneration exert toxic effects in neurons, which are in part mediated by cPLA 2 ␣ ( 182, 183 ). Genetic ablation of cPLA 2 ␣ improves cognitive function in a mouse model of familial Alzheimer's disease, and protects from the toxic effects of intra-cerebroventricular injection of A ␤ oligomers ( 184,185 ). A recent study found that A ␤ peptides activate cPLA 2 ␣ in rat primary cortical neurons, resulting in increased expression of ␤ -amyloid precursor protein by an autocrine pathway involving PGE 2 production and increases in cAMP ( 186 ).…”
Section: Reproductionmentioning
confidence: 99%